A role of endothelial dysfunction in development of maternal, perinatal and pediatric morbidity - A. V. Mironov; M. M. Umakhanova; A. M. Torchinov (IRBIS LLC, 2020)
Aim: to analyze an effect of endothelial dysfunction on development of obstetric, perinatal and pediatric pathology by using morphometric studies of peripheral blood desquamated endothelial cells (DECs).Materials and Methods. A prospective cohort clinical study included 163 female patients with singleton pregnancy. All pregnant women in the first trimester underwent DECs computer morphometry together with clinical and statistical examining course of pregnancy, labor as well as follow-up observation of born children under the age of 1 year.Results. The study demonstrated that endothelial damage in the first trimester of pregnancy profoundly affected maternal, perinatal and pediatric morbidity: detection of DECs in the first trimester with mean diameter less than 30 mkm increased probability of developing placental insufficiency by 52.0 %, preeclampsia - by 48.8 %, threatened preterm labor - by 32.4 %, premature detachment of the normally situated placenta - by 6.0 %. Identifying in DECs in the first trimester with mean diameter less than 40 mkm was associated with increased risk of acute fetal hypoxia in labor by 7.9 %, pediatric central nervous system disorders - by 37.9 %, increased rate of acute respiratory viral infections in children under 1 - by 17.3 %.Conclusion. Examining state of vascular endothelium in the first trimester of pregnancy represents an important component of prenatal diagnostics and opens up new avenue for prevention and treatment of obstetric, perinatal and pediatric pathology.